(untitled) (Cadernos de Sociomuseologia, 2022)
From an analysis of the research, teaching and extension actions developed in her teaching practice at the Federal University of Bahia and the Lusophone University of Humanities and Technologies of Lisbon, with Paulo Freire’s work as one of the main references, the authoress selects themes that generate the Freiriano universes and museology, approaches them and records that these were important foundations for the development of her walk as a museologist-educator-educanda. Analyzes the contexts, the different concrete realities in which the authoress was immersed and was gradually building dialogical and collaborative actions, approaching the work of the Master. Problematizes the reality of museums when enter the world of museology, analyzing the limits, silences and technicality. Broadens her reflections on the museal practices enriched in the dynamics of the social process, by suggesting the redefinition of the concept of museal fact and the inclusion of new actions to the process of musealization. Key-words: Paulo Freire; Education; Museology; Teaching; Research and Extension; Cultural Heritage; Museums.